2008
DOI: 10.1080/18811248.2008.9711473
|View full text |Cite
|
Sign up to set email alerts
|

In-Core SCC Growth Behavior of Type 304 Stainless Steel in BWR Simulated High-Temperature Water at JMTR

Abstract: Irradiation-assisted stress corrosion cracking (IASCC) is one of the critical concerns when stainless steel components have been in service in light water reactors for a long period. In-core IASCC growth tests have been carried out using the compact tension-type specimens of type 304 stainless steel that had been pre-irradiated up to a neutron fluence level around 1 Â 10 25 n/m 2 under a pure water simulated boiling water reactor (BWR) coolant condition at the Japan Materials Testing Reactor (JMTR). In order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…One unique CGR data set on sensitized 304 SSs measured in an operating BWR showed that much higher CGRs were observed at an incore position than at an out-of-core position and these corresponded to higher ECP for the in-core position [207]. In-core tests (in-pile or in-reactor tests) of SCC growth of irradiated SSs have been conducted in the Halden reactor [202,204] and the Japan Material Testing Reactor [208]. Figure 16 compares CGR data of 304 SSs from in-pile tests and PIEs in BWR NWC water conditions [208].…”
Section: In-core Iasccmentioning
confidence: 99%
See 1 more Smart Citation
“…One unique CGR data set on sensitized 304 SSs measured in an operating BWR showed that much higher CGRs were observed at an incore position than at an out-of-core position and these corresponded to higher ECP for the in-core position [207]. In-core tests (in-pile or in-reactor tests) of SCC growth of irradiated SSs have been conducted in the Halden reactor [202,204] and the Japan Material Testing Reactor [208]. Figure 16 compares CGR data of 304 SSs from in-pile tests and PIEs in BWR NWC water conditions [208].…”
Section: In-core Iasccmentioning
confidence: 99%
“…In-core tests (in-pile or in-reactor tests) of SCC growth of irradiated SSs have been conducted in the Halden reactor [202,204] and the Japan Material Testing Reactor [208]. Figure 16 compares CGR data of 304 SSs from in-pile tests and PIEs in BWR NWC water conditions [208]. Comparison of the in-core data with corresponding PIE data (ex-core, out-of-core or out-ofpile data) showed that the in-core CGRs were similar to or slightly higher than PIE data at high ECP in BWR water conditions.…”
Section: In-core Iasccmentioning
confidence: 99%
“…Due to lifetime extension of BWR, since integrity evaluation is one of the most serious problems to be taken into consideration, the behavior of these existing stress corrosion cracks, regardless of small one or long one, must be clarified to guarantee the safety of the system. So far, many researchers have studied the stress corrosion cracking behavior of long crack in austenitic stainless steels under simulated BWR environment using CT specimen together with AC or DC potential drop techniques for crack length measurement (5)- (8) and proposed models to explain SCC behavior (9)- (11) . Furthermore, relationship between crack growth rate (da/dt) and stress intensity factor (K) has been successfully obtained and compared with the existing reference curves, such as the JSME code for Nuclear Power Generation Plants (12) , the NRC NUREG-0313 Rev.2 (13) and the Swedish Nuclear Power Inspectorate's Regulations SKIFS (14) .…”
Section: Introductionmentioning
confidence: 99%